Investigating polymorphisms by bioinformatics is a potential cost-effective method to screen for germline mutations in Chinese familial adenomatous polyposis patients - YANG, JUN (Oncol Lett, 2016)
The aim of this study was to investigate germline mutations of the APC, MUTYH and AXIN2 genes in Chinese patients with familial adenomatous polyposis (FAP), and further assess the value of bioinformatics in screening the pathogenic changes predisposing to FAP. APC genes from 11 unrelated FAP patients in Yunnan province in China were firstly examined by exon-specific DNA sequencing. For samples without already known pathogenic changes predisposing to FAP in the APC gene, whole-gene sequencing of MUTYH and AXIN2 was performed. Mutational analysis of each gene was performed by bioinformatics. Eleven different types of APC polymorphisms were observed in the cohort of families analyzed. Of these polymorphisms, four were missense substitutions (V1822D, V1173G, P1760H and K2057), one was a nonsense substitution (S1196X), and six were silent substitutions (Y486Y, T449T, T1493T, G1678G, S1756S and P1960P). One missense mutation (Q335H) and two intronic substitutions (c.264+11G>A and c.420+35A>G) were detected in the MUTYH gene, and four synonymous mutations (I144I, P455P, P462P and L688L) and three intonic mutations (c.1060–77G>T, c.1060–287A>G and c.1060–282 A>G) of the AXIN2 gene were observed. In addition to the already reported pathogenic mutations, by using function assessment tools and databases, the synonymous substitutions observed in the APC gene of our samples were predicted to affect splicing regulation in the translation of mRNA, while the missense mutations observed in the APC gene and MUTYH gene were predicted to be disease-related polymorphisms; however, no functional effect of the mutations was observed in the AXIN2 gene. Comprehensive screening for germline mutations in APC, MUTYH and AXIN2 genes followed by prediction of pathogenicity using bioinformatic tools contributes to a cost-effective way of screening germline mutations in Chinese familial adenomatous polyposis patients.